Antisense oligonucleotides targeting the SMN2 promoter region enhance SMN2 expression in spinal muscular atrophy cell lines and mouse model. Issue 10 (9th December 2021) - Wang, Jia; Bai, Jinli; OuYang, Shijia; Wang, Hong; Jin, Yuwei; Peng, Xiaoyin; Ge, Xiushan; Jiao, Hui; Zou, Jizhen; He, Cai; Xiao, Ping; Song, Fang; et al.
Abstract: Spinal muscular atrophy (SMA) is an autosomal recessive neuromuscular disease caused by homozygous deletions or mutations in survival motor neuron gene 1 ( SMN1 ). Currently, the primary therapeutic strategy for SMA is to increase the level of SMN via correcting SMN2 splicing (nusinersen and risdiplam). However, some patients with SMA do not respond to such treatments, thereby warranting a need to develop new therapeutic strategies. We have previously reported that SMN2 expression is epigenetically regulated by DNA methylation levels of the SMN2 promoter region. In the present study, we determined that methyl-CpG-binding protein 2 (MeCP2) may bind to this critical promoter region (nt-167 to 43). Antisense oligonucleotides (ASO-P1 and ASO-P2) were designed to target the key methylation sites in the SMN2 promoter region, which enhanced the overall transcription and functional protein expression levels in the SMA cell lines. These results were similar to those observed in nusinersen-treated SMA cells. Moreover, a combined treatment of ASO-P1 and ASO-NUS in SMA cell lines further increases fl-SMN2 transcript and SMN protein levels. The delivery of ASO-P1 to the central nervous system of severe SMA mice corrected the molecular, pathological, and functional phenotypes of this disease and increased survival rates. Our findings suggest that the key methylation regions in the SMN2 promoter region may be a novel therapeutic target for SMA. Graphical abstract: